Mechanism involved in interleukin-21-induced phagocytosis in human monocytes and macrophages. (22nd November 2016) - Vallières, F; Girard, D
Summary: The interleukin (IL)-21/IL-21 receptor (R) is a promising system to be exploited for the development of therapeutic strategies. Although the biological activities of IL-21 and its cell signalling events have been largely studied in immunocytes, its interaction with human monocytes and macrophages have been neglected. Previously, we reported that IL-21 enhances Fc gamma receptor (FcRγ)-mediated phagocytosis in human monocytes and in human monocyte-derived macrophages (HMDM) and identified Syk as a novel molecular target of IL-21. Here, we elucidate further how IL-21 promotes phagocytosis in these cells. Unlike its ability to enhance phagocytosis of opsonized sheep red blood cells (SRBCs), IL-21 did not promote phagocytosis of Escherichia coli and zymosan by monocytes and did not alter the cell surface expression of CD16, CD32 and CD64. In HMDM, IL-21 was found to enhance phagocytosis of zymosan. In addition, we found that IL-21 activates p38, protein kinase B (Akt), signal transducer and activator of transcription (STAT)-1 and STAT-3 in monocytes and HMDM. Using a pharmacological approach, we demonstrate that IL-21 enhances phagocytosis by activating some mitogen-activated protein kinases (MAPKs) and phosphoinositide 3-kinase (PI3K)–Akt and Janus kinase (JAK)–STAT pathways. These results obtained in human monocytes and macrophages have to be considered for a better exploitation of the IL-21/IL-21R system for therapeutic purposes. Graphical Abstract: